2017
DOI: 10.3390/su9050814
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Willingness to Pay a Premium for Eco-Labeled LED TVs in Korea: A Contingent Valuation Study

Abstract: Abstract:Although the production costs and prices of eco-labeled products are higher than those of conventional ones, the use of greener products can lead to better environmental outcomes. Thus, the consumers' preferences for eco-labeled products should be investigated to understand the potential of markets with green products. This study attempts to examine the consumers' preference or willingness to pay (WTP) a premium for eco-labeled products using a specific case study of a 43-inch LED TV, which is a commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Consumers' Willingness to Pay a Premium for Eco-Labeled LED TVs in Korea: A Contingent Valuation Study [12] assesses WTP for a popular eco-friendly LED TV by using a sophisticated contingent valuation method. The estimated WTP amounts to about 4% of the price of the TV and is higher for high-income, older, highly-educated, and female consumers with children.…”
Section: Miscellaneous Topicsmentioning
confidence: 99%
“…Consumers' Willingness to Pay a Premium for Eco-Labeled LED TVs in Korea: A Contingent Valuation Study [12] assesses WTP for a popular eco-friendly LED TV by using a sophisticated contingent valuation method. The estimated WTP amounts to about 4% of the price of the TV and is higher for high-income, older, highly-educated, and female consumers with children.…”
Section: Miscellaneous Topicsmentioning
confidence: 99%
“…The willingness of households to pay a price premium for products in various parts of the world has been analysed by many scientists [15,16,17,18,19,20]. However, already in 2010, Aichlmayr [21] observed that: “In recent years, green consumption and marketing have triggered close attention and investments from producers”.…”
Section: Introductionmentioning
confidence: 99%
“…In his study he measured the preferences and willingness of consumers to pay for coffee labeled certification in Taiwan, with certification results that are easily known, organic, the level of certification of products that are environmentally friendly, and shows that fair trade will make consumers willing to pay more. Ecolabeling tends to be an important factor in influencing consumer purchasing decisions, when the price of green products is relatively expensive or of low quality, in other words the product attributes of ecolabels have a dominant role compared to other product attributes [30] when consumers will decide to buy it at a higher price than conventional products.. Research shows the same results, that consumers are willing to pay more for the price of electrocable products, such as 43-inch LED TVs for consumers in Korea [25] , and seafood [34]. From this description, I propose the following hypothesis : H2 : Ecolabel is thought to influence the Consumers' Willingness to Pay More.…”
Section: Literature Reviewmentioning
confidence: 82%